Transosseous Tie Fixation Using Krackow Sutures and Bone Tunnels in a Comminuted Fracture of the Upper Pole of the Patella: A Case Report - Jong Seok Baik (Journal of Trauma and Injury)
Comminuted fractures of the patella mostly occur at the inferior pole and require appropriate reduction and fixation to restore the extensor mechanism. Conventional methods such as tension-band wiring are not enough to gain proper fixation strength. Numerous methods have been reported, including circumferential cerclage wiring, osteosynthesis, and suture anchors depending on the fracture pattern. Herein, the author reports a relatively rare case of a comminuted fracture of the upper pole of the patella, for which we used augmented Krackow sutures in the quadriceps and fixation with tying of the suture limbs through patellar bone tunnels. Satisfactory results were obtained in terms of reduction and extensor mechanism recovery.